A critical study of the teaching attitudes of teachers at primary school level in Pakistan. (13th October 2021) - Saeeda, Bibi; Noor, Tahmina; Ullah, Arif; Aznaoui, Hanane
The research was conducted on the topic of 'critical study of the teaching attitudes of teachers at primary level in government girl's primary schools in (KPK) Pakistan'. The main objectives of the study were to find out positive aspects of teachers' teaching attitudes, to explore negative aspects of teachers' teaching attitudes and to provide suggestions for improving teaching attitudes. For this purpose the descriptive type research was carried out. A total of 175 primary schools for girls in (KPK) Pakistan was selected. All students of class five which make a total of 1, 560 students; came under the population of the present study. The study was delimited to 100 government primary schools for girls, 500 students were the sample size of the study. Five students of class 5th were randomly selected from each school. A structured questionnaire was used each question of the questionnaire was having three answers, i.e., yes, no and somewhat. The data collected from the field was analysed through software Statistical Package for Social Science. Conclusion was made on the basis of these findings. From the study, it was concluded that the teachers' teaching attitudes of government girls' primary schools in Pakistan is positive except that they do not encourage co-curricular activities.